British psychoanalysis and politics - Young, Robert M. (PINS-Psychology in Society, 2026)
The first thought this title brings to mind is that it is inappropriate, since British psychoanalysis is ostensibly apolitical, but this is quickly followed by the certain knowledge that to be "apolitical" is to tolerate the status quo. British psychoanalysis is centrist in the sense that most of its practitioners are neither socialists nor ultra-conservatives as voters, upper middle class economically and socially, and their clientele are the same. These descriptions are true, if only because there is practically no psychoanalysis or psychotherapy available on the National Health Service, so they are, for the most part, available only to people who can pay, on average, twenty pounds per session. There are some "low fee" clinics, and a few places in some National Health Service clinics, but these are likely to be group therapy or short-term. The other thing to be said about British psychoanalysis is that it is not one thing. Only members of the British Psycho-analytical Society can call themselves psychoanalysts. There are about four hundred members, a fair number of whom live abroad. There are only about a dozen new candidates per year in training. It is said that because the American non medical psychotherapists successfully sued the medical psychoanalysts for being "in restraint of trade", that is, in effect, operating a form of monopoly, there are plans afoot to broaden entry to the International Psychoanalytic Association.